Newborn screening for sickle cell disorders using tandem mass spectrometry: three years' experience of using a protocol to detect only the disease states. (September 2017) - Moat, Stuart J; Rees, Derek; George, Roanna S; King, Lawrence; Dodd, Alan; Ifederu, Adeboye; Ramgoolam, Tejswurree; Hillier, Sharon
Background: Tandem mass spectrometry (MS/MS) has recently become an alternative method for the newborn screening of sickle cell disorders (SCD), as it is able to detect haemoglobin (Hb) peptides following digestion of bloodspots with trypsin. Using the SpOtOn Diagnostics Reagent Kit, we previously developed a screening protocol to detect only the disease states of SCD, using action values based on the ratio between the variant Hb peptide to wild-type peptide abundances for the HbS, C, D Punjab, O Arab, E and Lepore peptides. Methods: Action values using the ratios between the wild type HbA (ßT1-3) peptides and the foetal Hb (γT2) peptide were developed to identify bloodspot samples from premature and transfused infants. An evaluation was undertaken to assess the transferability of the action values onto an additional MS/MS instrument. We report here our experience using this MS/MS protocol. Results: During a three-year period, we screened 100, 456 babies and identified 10 SCD cases (1 HbS/HPFH, 5 HbS/S and 4 HbS/C) and a case of HbE/ß-thalassaemia that was identified as a by-product. The Hb variant to wild-type peptide ratio action values were transferable to a second MS/MS instrument. Our protocol prevented the identification of an estimated 810 carrier infants. Gestational age-related action values for HbA to HbF peptide ratios were required to minimize the number of samples referred for second-line testing to exclude ß-thalassaemia. Conclusion: MS/MS is a robust alternative screening technology for SCD; in addition, it also optimizes the use of equipment and expertise that currently exist in newborn screening laboratories.